Do Groin Drains Reduce Postoperative Morbidity in Women Undergoing Inguinofemoral Lymphadenectomy for Vulvar Cancer?. Issue 1 (January 2018) - Pontre, Jennifer; Harding, Julia; Chivers, Paola; Loughlin, Leah; Leung, Yee; Salfinger, Stuart G.; Tan, Jason; Mohan, Ganendra R.; Cohen, Paul A.
Abstract : Objective: Sentinel lymph node biopsy has been widely adopted in the surgical management of women with early-stage vulvar cancer, but many patients require inguinofemoral lymphadenectomy (IFL). Following IFL, many surgeons drain the groin to prevent lymphocyst formation despite a lack of evidence to support this practice. Our objective was to investigate whether groin drains after IFL are associated with reduced postoperative morbidity in women undergoing surgery for vulvar cancer. Methods: A retrospective cohort study of women diagnosed as having primary vulvar cancer who underwent vulvectomy/radical local excision and unilateral or bilateral IFL was conducted. Cases were ascertained from the weekly outcome reports of a statewide tertiary gynecologic oncology tumor board. Data including postoperative outcomes were abstracted from medical records. Patients were stratified into 1 of 2 groups according to whether a groin drain had been used. Results: Seventy-one patients were included. Inguinal drains were used in 48 patients (67.6%) and 23 patients (32.4%) did not have their groin wound(s) drained. The most common postoperative complications recorded were wound infection (59.2%), groin lymphocyst (32.4%), and cellulitis (25.4%). The mean length of hospital admission was 11.5 days (2–40 days). Compared with patients in whom inguinal drains were placed, those in the "no drain" group had a significantly lower incidence of postoperative groin cellulitis (8.7% vs 25.4% P = 0.039). No significant differences were observed between patients in the "drain" and "no drain" groups in lymphocyst formation, wound infection, return to the operating room, duration of hospital stay, readmission post-discharge, and lower-limb lymphedema. Conclusions: In this study of patients undergoing inguinofemoral dissection for primary vulvar cancer, postoperative cellulitis occurred less frequently in patients without an inguinal drain. The incidence of other postoperative complications was no different whether or not a groin drain was used. Prospective studies may be warranted.